Promoting Your Brand Through Audio Narration: Examining the Potentials of Podcast Advertising in Indonesia - Marbun, Imam Asma Nur Alam (Jurnal Komunikasi, 2023)
The world is entering the Golden Age of Podcasting, as evidenced by the amount of podcast consumption that continues to grow and is predicted to continuously increase. The rapid progress of this new medium has not gone unnoticed by advertising practitioners. The closeness formed through parasocial interactions between listeners and broadcasters makes podcast platforms a soft ground for advertising due to the low resistance of listeners to advertisements that are perceived through story narration. This study is carried out by combining qualitative and quantitative approaches to measure the potential of podcast advertising in Indonesia through a case study of one of the most popular podcast programs in Indonesia, which is Podkes Kesehatan Masyarakat (Podkesmas). Using literature study and observation methods, researchers are trying to identify Podkesmas profiles and their advertising approaches. After that, using quantitative methods through a purposive survey of Podkesmas listeners, this study aims to find out whether listeners do feel the closeness to podcasters (audience-host relationship), whether such proximity positively affects listeners' attitudes towards podcast ads, whether that proximity affects listeners' consumption of the advertised product, and whether the way the broadcaster delivers the ad affects the listener's intention to purchase the advertised product. The results of the linear regression found that there is indeed an emotional closeness between listeners and podcasters that causes listeners' positive attitudes toward podcast ads. However, this emotional proximity does not significantly affect their consumption of the advertised product. In addition, the approach of delivering ads using narration also does not significantly predict the consumption behavior of podcast listeners.